Entamoeba histolytica meningoencephalitis diagnosed by trophozoites in cerebrospinal fluid - Goh, L M L (BlackWell Publishing Ltd, 2013)
Entamoeba histolytica meningoencephalitis has not been described in the modern literature, which is distinct from that caused by free-living amoebae. We report the first case of E. histolytica meningoencephalitis without liver or brain abscesses. Cerebrospinal fluid revealed 2 + very motile trophozoites. Our patient was successfully treated with intravenous metronidazole.